Regional variation of human pancreatic islets dimension and its impact on beta cells in Indian population. Issue 6 (2nd November 2019) - Ravi, Praveen Kumar; Purkait, Suvendu; Agrawal, Usha; Patra, Susama; Patnaik, Madhumita; Singh, Sudipta Ranjan; Mishra, Pravash Ranjan
ABSTRACT: Background & objectives : Islet of Langerhans, the endocrine pancreas plays a significant role in glucose metabolism. Obesity and insulin resistance are the major factors responsible for beta cell dysfunction. Asian Indian population has increased susceptibility to diabetes in spite of having lower BMI. The morphology of islets plays a significant role in beta cell function. The present study was designed for better understanding the morphology, composition and distribution of islets in different parts of the pancreas and its impact on beta cell proportion. Methods : We observed islet morphology and beta cell area proportion by Large-scale computer-assisted analysis in 20 adult human pancreases in non-diabetic Indian population. Immunohistochemical staining with anti-synaptophysin and anti-insulin antibody was used to detect islet and beta cells respectively. Whole slide images were analyzed using ImageJ software. Results : Endocrine proportion were heterogeneously increasing from head to tail with maximum islet and beta cell distribution in the tail region. Larger islets were predominately confined to the tail region. The islets in Indian population were relatively smaller in size, but they have more beta cells (20%) when compared to American population. Interpretation & conclusions : The beta cells of larger islets are functionally more active than the smaller islets via paracrine effect. Thus, reduction in the number of larger islets may be one of the probable reasons for increased susceptibility of Indians to diabetes even at lower BMI. Knowledge about the regional distribution of islets will help the surgeons to preserve the islet rich regions during surgery.